ANALYSIS OF THE INFLUENCE OF STORE IMAGE, WORD OF MOUTH (e-WOM), THE PERCEPTION OF PRICE ON PURCHASE DECISIONS RE-FOOD ANIMALS - Putri Permatasari, Evi; Sumarto, Laksono; Suharyoko, Suharyoko (IJBLE Scientific Publications Community Inc., 2023)
Viva Pet Shop Sukoharjo through social media to promote a product and form a community or a group online with consumers who like the brand-brand food products of animals that are used to develop a community or a group online that allows the occurrence of a social interaction electronically that encourage the occurrence of electronic word of mouth. Electronic word of mouth is positive or negative statements made by potential customers, customers ' actual and former customers about a product or company through the internet. The purpose of this study is to determine whether there is a simultaneous influence of brand image, Word of Mouth (e-WOM), and the perception of price on consumer purchase decisions in a Pet Shop Sukoharjo. This research is quantitative descriptive using multiple linear regression analysis and hypothesis test. Data collection using a questionnaire. The results of this study stated that there is the influence of the interaction between store image, Word of Mouth, and the perception of price on consumer purchase decisions in a Pet Shop.